The effect of sodium‐glucose cotransporter‐2 inhibitors on inflammatory biomarkers: A meta‐analysis of randomized controlled trials - Jeffrey Stephens (Diabetes, Obesity and Metabolism, 2024)
Aims: To conduct a meta-analysis of randomized controlled trials (RCTs) to assess the effect of sodium-glucose cotransporter-2 (SGLT2) inhibitors on inflammatory biomarkers. Methods: Medline, Embase and the Cochrane Library were searched for RCTs investigating the effect of SGLT2 inhibitors on inflammatory biomarkers, adipokine profiles and insulin sensitivity. Results: Thirty-eight RCTs were included (14 967 participants, 63.3% male, mean age 62 ± 8.6 years) with a median (interquartile range) follow-up of 16 (12–24) weeks. Meta-analysis showed that SGLT2 inhibitors significantly improved adiponectin, interleukin-6, tumour necrosis factor receptor-1 (vs. placebo alone: standardized mean difference [SMD] 0.34 [95% confidence interval CI 0.23, 0.45], mean difference [MD] −0.85 pg/mL [95% CI −1.32, −0.38], SMD −0.13 [95% CI −0.20, −0.06], respectively), leptin and homeostatic model assessment of insulin resistance index (vs. control: SMD −0.20 [95% CI −0.33, −0.07], MD −0.83 [95% CI −1.32, −0.33], respectively). There were no significant changes in C-reactive protein (CRP), tumour necrosis factor-α, plasminogen activator inhibitor-1, fibroblast growth factor-21 or monocyte chemoattractant protein-1. Conclusions: Our analysis shows that SGLT2 inhibitors likely improve adipokine biomarkers and insulin sensitivity, but there is little evidence that SGLT2 inhibitors improve other inflammatory biomarkers including CRP.